2020 International Conference on Recent Trends on Electronics, Information, Communication &Amp; Technology (RTEICT) 2020
DOI: 10.1109/rteict49044.2020.9315726
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Employees under Stress for Pre-emptive Remediation using Machine learning Algorithm

Abstract: With the ongoing COVID-19 pandemic, businesses and organizations have acclimated to unconventional and different working ways and patterns, like working from home, working with limited employees at office premises. With the new normal here to stay for the recent future, employees have also adapted to different working environments and customs, which has also resulted in psychological stress and lethargy for many, as they adapt to the new normal and adjust their personal and professional lives. In this work, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…2. The results give new suggestions to improve workplaces in terms of improving the Mental Health of their employees, which are not covered by sources such as [15], where role ambiguity, age and working hours were the influential critical factors found affecting Mental Health. Our study finds that the ease of leave accessibility, how supportive companies are to Mental Health concerns, and the overall importance companies place on Mental Health were all key factors influencing employees' Mental Health.…”
Section: Contribution To Existing Gaps In the Fieldmentioning
confidence: 97%
See 2 more Smart Citations
“…2. The results give new suggestions to improve workplaces in terms of improving the Mental Health of their employees, which are not covered by sources such as [15], where role ambiguity, age and working hours were the influential critical factors found affecting Mental Health. Our study finds that the ease of leave accessibility, how supportive companies are to Mental Health concerns, and the overall importance companies place on Mental Health were all key factors influencing employees' Mental Health.…”
Section: Contribution To Existing Gaps In the Fieldmentioning
confidence: 97%
“…and the associated modified working conditions, a problem bearing great relevance to the present day. Specifically, they utilize an XGBoost Classifier to obtain a relatively high F1-score (see section 4.4 for an explanation of this metric) of 0.82 [15]. Their feature importance analysis found that working hours, age, and role ambiguity had the most significant negative impact on employee performance.…”
Section: Garlapati Et Al Use ML Algorithms To Predict Employer Stress...mentioning
confidence: 99%
See 1 more Smart Citation
“…With the improvement of big data analytics, technology starts concentrating on disease prognosis from the perspective of big data analysis 8 . Several researches were carried out for selecting the property automatically from various data, for improving the performance of the risk classification, instead of formerly‐selected features 9 . Therefore, in the last few years, several studies focused heavily on convolution neural networks (CNNs), logistic regression (LR), support vector machines (SVMs), machine on machine learning‐based disease prognosis (ML), 10 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…8 Several researches were carried out for selecting the property automatically from various data, for improving the performance of the risk classification, instead of formerly-selected features. 9 Therefore, in the last few years, several studies focused heavily on convolution neural networks (CNNs), logistic regression (LR), support vector machines (SVMs), machine on machine learning-based disease prognosis (ML), 10 and so on. During the testing process, input information is categorized into different classes.…”
mentioning
confidence: 99%